2022
DOI: 10.1155/2022/4613165
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Mothers Diversified Dietary Intake and Associated Factors in Southwest Ethiopia: A Cross-Sectional Study

Abstract: Background. Dietary diversity is very critical for fetal growth and development, as well as for the health and wellbeing of the mother. In Ethiopia, 41% of pregnant mothers consume diversified diets. There has been no study assessing whether pregnant women in southwest Ethiopia consume a varied diet. Objective. To estimate the proportion of adequate diversified dietary intake and to determine whether there is an association between diversified dietary intake and mothers’ social capital. Design. A community-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Considering a single population proportion formula, the sample size was determined with the assumption of a proportion (p) of good diet diversity practice among pregnant individuals in Southwest Ethiopia, which was 14.7% 29 . 95% confidence level (Z α/2) and 0.05 expected margin of error (d).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering a single population proportion formula, the sample size was determined with the assumption of a proportion (p) of good diet diversity practice among pregnant individuals in Southwest Ethiopia, which was 14.7% 29 . 95% confidence level (Z α/2) and 0.05 expected margin of error (d).…”
Section: Methodsmentioning
confidence: 99%
“…Similar research in Sudan indicated that superior habits in terms of food selection and dietary diversity scores were demonstrated by greater knowledge 28 . Numerous studies have been conducted on dietary practices and their determinants among pregnant women in Ethiopia 29 32 , but there is a gap in the evidence concerning these practices among pregnant adolescents. Pregnant adolescents continue to constitute an underserved population; therefore, this study sought to close this gap by examining dietary practices and associated factors among pregnant adolescents in the West Arsi Zone, Central Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, Malon et al (2010) 135 y Roos et al (1998)136 encontraron que las mujeres que cuentan con pareja tienen más probabilidades de adherirse a un patrón de alimentación saludable, comparadas con las solteras. Tariku & Baye(2022) encontraron que la diversidad en la ingesta de alimentos durante el embarazo se asocia con tener empleo remunerado y apoyo emocional del esposo 137. Kiboi et al (2017), también observaron que el contar con un salario propio se relaciona con mayor probabilidad de tener una dieta más diversa durante el embarazo.…”
unclassified